(3eNJUQ MGWH djds - (3Jbj GdOjf jMji Hf eMeO Hf jhSa GdSYjOj, GHf GdcQeGfjs; (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3eMeO EHQGgje GdYfGfj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg QH GdYGdejf aEf gPg JPcQI aef TGA EJNP Edi QHg SHjdG jG bGFejf Edi GdUdGI HWjHI fdJe ebGekG HGdfHj YXjeG s
(3BNQgG (B:s
(3SGhe CTYH JGLQkG aj LHg hTi hjJdhg aj GdLRA GdKGfj, bGd GHf Ybjd GdMfHdj aj cdGe LQi hGdMeO ddg s
(3CJe ENJUGQg aj GdbGgQI SfI (B828(3g```s
(3HgG fXGe GdJYbjHIs
(3MGWH djd dCHj GdYHGS TgGH GdOjf CMeO Hf jMji Hf CHj HcQ GdJdeSGfj GHf CHj MLdI GdeJhai (B776(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs